The effect of early in‐hospital medication review on health outcomes: a systematic review. (3rd June 2015) - Hohl, Corinne M.; Wickham, Maeve E.; Sobolev, Boris; Perry, Jeff J.; Sivilotti, Marco L. A.; Garrison, Scott; Lang, Eddy; Brasher, Penny; Doyle‐Waters, Mary M.; Brar, Baljeet; Rowe, Brian H.; Lexchin, Joel; et al.
<x xml:space="preserve">Abstract</x> Aims Adverse drug events are an important cause of emergency department visits, unplanned admissions and prolonged hospital stays. Our objective was to synthesize the evidence on the effect of early in‐hospital pharmacist‐led medication review on patient‐oriented outcomes based on observed data. Methods We systematically searched eight bibliographic reference databases, electronic grey literature, medical journals, conference proceedings, trial registries and bibliographies of relevant papers. We included studies that employed random or quasi‐random methods to allocate subjects to pharmacist‐led medication review or control. Medication review had to include, at a minimum, obtaining a best possible medication history and reviewing medications for appropriateness and adverse drug events. The intervention had to be initiated within 24 h of emergency department presentation or 72 h of admission. We extracted data in duplicate and pooled outcomes from clinically homogeneous studies of the same design using random effects meta‐analysis. Results We retrieved 4549 titles of which seven were included, reporting the outcomes of 3292 patients. We pooled data from studies of the same design, and found no significant differences in length of hospital admission (weighted mean difference [WMD] –0.04 days, 95% confidence interval [CI] –1.63, 1.55), mortality (odds ratio [OR] 1.09, 95% CI 0.69, 1.72), readmissions (OR 1.15, 95% CI 0.81, 1.63) or emergency department revisits at 3 months (OR 0.60, 95% CI 0.27, 1.32). Two large studies reporting reductions in readmissions could not be included in our pooled estimates due to differences in study design. Conclusions Wide confidence intervals suggest that additional research is likely to influence the effect size estimates and clarify the effect of medication review on patient‐oriented outcomes. This systematic review failed to identify an effect of pharmacist‐led medication review on health outcomes.